Dermoscopic and reflectance confocal microscopic presentation of Hailey-Hailey disease : a case series - Pimentel, Bernardo Vaz Ruivo Vasconcelos (2018)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2017